ВТОРИННІ НАЗВИ ЯК ОДИН ІЗ ЗАСОБІВ РЕАЛІЗАЦІЇ СТОМАТОЛОГІЧНОГО ДИСКУРСУ / SECONDARY TITLES AS MEANS OF IMPLEMENTATION OF DENTAL DISCOURSE - Лариса ШУТАК (Aktualʹnì Pitannâ Suspìlʹnih Nauk ta Istorìï Medicini, 2017)
Лариса Шутак. Вторичные наименования как один из способов реализации стоматологического дискурса. Рассмотрены в частности вторичные лексемы – названия инструментов, деталей инструментов; названия органов и их частей, создаваемых за внешним сходством. Исследовано также вторичные названия, возникающих на основе ассоциативных связей, в результате метафорических и метонимии переносов. Ключевые слова: номинация, вторичная номинация, способы номинации, стоматологическая лексика, стоматологический дискурс. Shutak Larysa. Secondary Titles as Means of Implementation of Dental Discourse. Lexical organization of any language is characterized not only by correlation of existing language lexicalsemantic units but also by rethinking its ability to name everything that is necessary for the speaker at the moment. So often in the speech secondary names appear, ie the formation of a second, even a third name for extra-linguistic reality of objects that have been tagged by means of language. These tokens now actively occur, the evidence of this is the emergence of a large amount of secondary nomination is not yet certified by dictionaries, but the language used in practice. Since modern dentistry is a branch of clinical medicine that studies diseases of the teeth, mucous membranes and other parts of the mouth, jaw and face, and dental vocabulary is a part of clinical terminology, one of the most difficult medical terminology, mostly of Greek origin, it was necessary to analyze ways of creation of secondary nomination in dental discourse (based on dental vocabulary). Article processed secondary names, tailored with domestic broadcasting dentists found the causes of these names, especially their creation and use. Particularly secondary tokens, such as the names of tools, parts, tools; and the names of their parts created by external similarity are considered. The author studied secondary names that appear based on associative connections due to analogical and metaphorical transfers from numerical comments on the use of nouns, such as names teeth that substitutes terminological combinations. Key words: nomination, secondary nomination, nomination methods, dental vocabulary, dental discourse.